Compression and Implicitness Through Dependent Phrases in Academic ESL Writing by Filipino Researchers Across Disciplines - Hernandez, Hjalmar Punla; Genuino, Cecilia F. (LEARN Journal: Language Education and Acquisition Research Network, 2022)
Grammatical compression and implicitness have been proven as characteristics of academic writing (Biber & Gray, 2010, 2016), but they are an underexplored area of research particularly in academic ESL (English as a second language) writing. In this study, we explored the dependent phrases that most and least characterize academic ESL writing by cross-analyzing 42 published research articles (RAs) authored by Filipino researchers (FRs) in Curriculum and Instruction, Communication, and Psychology using Biber et al.’s (1999, 2021) framework. Salient findings showed that attributive adjectives, nominal prepositional phrases, and noun premodifiers had the highest frequencies of use, thus most characterizing academic ESL writing across disciplines. In contrast, prepositional phrases as adverbials and appositive noun phrases as noun postmodifiers had the lowest occurrences, hence least characterizing academic ESL writing. We argue that academic ESL writing regardless of its discipline is highly packed with dense information by the three most common nominal modifiers. Our study has applied implications for teaching academic writing, assessing academic writing, and publishing academic research.